Distant Early Warning (DEW) Line: Integrated Cultural Resources Management Plan - 611th Civil Engineer Squadron (2013)
Aerial photographs of various radar sites from the Distant Early Warning (DEW) Line: Integrated Cultural Resources Management Plan (2013)